Evaluation of the Influence of Ground Wastes Glass on Mechanical Properties of High Performance Concrete - Auwal, A. M.; Mtallib, M. O. A.; Abdulwahab , M. T.; Mohammed, A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
The construction industry is largely reliant on the use of cement-based products. Every tonne of ordinary Portland cement (OPC) emits equivalent amount of CO2 into the atmosphere, contributing to increased raw material consumptions and environmental concerns. In this regard, the use of waste materials that can be blended with OPC as partial or full replacement to reduce the environmental impacts is strongly desirable. This research was experimentally carried out to evaluate the influence of ground waste glass (GWG) as a partial replacement of cement in high performance concrete (HPC). A grade 50 HPC was designed based on ACI 211.1-91. Various experiments were carried out to determine the mechanical properties of the HPC. Tests include specific gravity of constituent materials, sieve analysis of GWG and aggregates, slump flow of fresh HPC, compressive, splitting tensile and flexural strengths of hardened HPC were carried out. The chemical composition analysis of GWG was conducted using X-Ray Fluorescence (XRF) analytical method. HPC cubes, cylinders and beams were cast, cured and tested at curing ages of 3, 7, 28, 56 and 90 days using 0, 5, 10 15, 20 and 25 percentage replacement levels. The optimum compressive strength of 57.44 N/mm2 was obtained at 10% cement replacement after 28 days of curing age. The slump test result shows that the workability of the HPC decreased as the GWG content increases. Generally, the strengths of HPC reduced as the percentage of GWG replacement increased beyond 10% but increases with curing age. Therefore, 10% is the optimum replacement level of GWG for cement in HPC.